Development of problem orientation model and work organization in problem-based learning at Muhammadiyah Senior High School of Batu city - N. Nurwidodo; Siti Zaenab; Iin Hindun; Sri Wahyuni (University of Muhammadiyah Malang, 2025)
The problem-based learning (PBL) model consists of five steps: orienting students to the problem, organizing work, guiding investigations, compiling work and presenting it, and evaluating the process and results. However, many teachers have not implemented the first and second steps properly, so that the goal of developing students' critical and creative thinking is not achieved. This study aims to develop a problem orientation and work organization model in PBL. This study uses the ADDIE model (Analysis, Design, Develop, Implementation, and Evaluation). The results of the analysis show that teachers still have difficulty in implementing PBL steps and need more operational guidance. The model developed includes systematic steps to formulate problems and organize student work to be more effective. The validation results show that this model is valid and has been tested practically, with positive responses from teachers to its implementation. This guide can improve the effectiveness of PBL teaching, ensure its implementation is in accordance with the correct concept, and minimize errors in learning practices.